(untitled) (Nigerian Journal of Technology, 2002)
A closed cycle solid absorption intermittent refrigerator, using CaC12 absorbent and NH3 refrigerant, was constructed and tested to obtain the instantaneous and cumulative available overall COP. The combined collector/absorber/generator unit had double glazing of 1.14 m2 exposed areas. The system was fitted with a stagnant passive evaporative condenser with porous sandcrete wall, which produced condenser water temperatures varying from 3 – 10 deg C below ambient, during NH3 generation and condensation. The instantaneous available overall COP rose to a peak which depended on the solar fluxes and starting pressure, as well as on the condenser and ambient temperatures. The peak varied from 0.07 to 0.08. It fell as solar flux decreased towards late afternoon, but rose again slightly due to the combined effect of decreasing collector plate temperature and solar flux. The cumulative overall COP rose steadily to peak values in the range of 0.07 to 0.08, by the end of the generation period. The COP was a strong function of starting generator pressure or evaporating temperature, and fell as the pressure decreased. The cumulative overall COP is much lower than the peak instantaneous COP as a result of system inertia, caused by high collector plate and tube mass, and large system free volume. The refrigerator is capable of maintaining evaporator temperature of -10 OC during the cooling phase, and is well suited for vaccine and food storage applications.